Desktops, Mobiles & E-Commerce: The Uneven Tech Landscape of Today’s Businesses - Shrestha, Shraddha; Shrestha, Sneha; Kurungwang Limbu, Suraj; Basnet, Asmita; Thapa, Bala Ram (People's Journal of Management, 2025)
Background: The rapid digital transformation of businesses has created disparities in technology adoption across industries and gender groups. While some sectors embrace advanced tools like e-commerce and mobile platforms, others lag due to structural, cultural, or resource-related barriers. Understanding these variations is critical for fostering inclusive digital growth and optimizing workplace efficiency. Objective: This study examines gender and sector-based differences in technology usage, focusing on desktops, mobiles, e-commerce, and communication tools. It aims to identify adoption gaps and assess whether traditional divides persist in today’s digital economy. Methods: A quantitative survey of 196 professionals across multiple industries (services, agriculture, manufacturing, etc.) was conducted. Independent samples t-tests analyzed gender differences, while Tukey’s post-hoc tests compared sector-wise technology adoption. Variables included fixed telephony, mobile devices, desktops, laptops, internet, social media, e-commerce, and e-marketing tools. Findings: Gender disparities were minimal except in laptop usage, where males reported significantly higher adoption. Sectoral analysis revealed that service industries lead in mobile and internet use, while construction/utilities rely more on fixed telephones. Wholesale/retail trade showed the lowest digital engagement, whereas e-commerce adoption was uniform across sectors. Conclusion: While digital gender gaps are narrowing, sector-specific divides remain pronounced. Infrastructure-heavy industries depend on traditional tools, whereas customer-facing sectors prioritize modern platforms. E-commerce has achieved widespread adoption, suggesting its universal importance in business operations. Implications: Policymakers and business leaders should develop targeted strategies to address sector-specific adoption barriers and promote equitable technology access. Future research should explore underlying causes, such as training gaps or economic constraints, to support inclusive digital transformation.